Peran Pengelola UMKM Olahan Sagu dalam Meningkatkan Kemandirian Ekonomi Karyawan di Desa Banglas Barat Kabupaten Kepulauan Meranti - Ninik Sumarni; Kodarni Kodarni (Yayasan Almanar Pujud, 2024)
This research is based on the establishment of sago processed (SMEs) in West Banglas Village, there are many employees who are members there, whether (SMEs) in West Banglas Village can increase economic independence. The purpose of this study is to find out how far the role of sago processed MSME managers is in increasing the economic independence of employees in West Banglas Village, Meranti Islands Regency. The number of informants in this study was five people. This research method uses qualitative research methods, with observational data collection techniques, interviews and documentation. Based on the results of the research conducted by the researcher, it can be concluded that the role of sago processed MSME managers in increasing economic independence has played a role as training in terms of providing skills and knowledge, as assistance in terms of increasing income, as organizing in terms of opening job opportunities, as a motivator.